Masa depan pendidikan dengan AI : analisis potensi dan resiko dalam transformasi perguruan tinggi - Trisnawati, Fidian (Maliki Interdisciplinary Journal, 2025)
Artificial Intelligence (AI), particularly ChatGPT, has significantly impacted higher education in Indonesia. AI enhances the efficiency of teaching and learning processes by assisting students in understanding complex materials, completing academic assignments, and accessing various learning resources quickly and practically. However, unwise use of AI poses serious risks, such as the decline of critical thinking skills, increased plagiarism, and overdependence on technology. Therefore, it is essential to regulate AI usage in education through ethical and proportional approaches. Students must be guided to use AI as a learning aid rather than a substitute for the learning process itself. Likewise, educational institutions and educators should encourage the integration of technology while still emphasizing the development of thinking skills, creativity, and academic integrity. With a b alanced approach, AI can serve as a strategic partner in shaping a competent generation ready to face the digital era..